2000
DOI: 10.1354/vp.37-3-248
|View full text |Cite
|
Sign up to set email alerts
|

p53 Gene Mutations Occurring in Spontaneous Benign and Malignant Mammary Tumors of the Dog

Abstract: Sixty-three cases of benign and malignant canine mammary tumors were analyzed to define the alteration of exons 5-8 for the p53 tumor suppressor gene using polymerase chain reaction direct sequence analysis with paraffin-embedded tissues. Four missense mutations were found in 38 benign mammary tumors (11%), and five missense (one tumor had two missense mutations) and one nonsense mutations were found in 25 mammary carcinomas (20%). These data suggest that the p53 gene alterations might be initiated at an early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 14 publications
(43 reference statements)
1
31
1
1
Order By: Relevance
“…Remarkably, several canine position 249 point mutations reported so far are CGG → TGG transitions (arginine → tryptophan). They concerned two mammary (Mayr et al, 1998;Muto et al, 2000) and one circumanal gland tumour (Mayr et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, several canine position 249 point mutations reported so far are CGG → TGG transitions (arginine → tryptophan). They concerned two mammary (Mayr et al, 1998;Muto et al, 2000) and one circumanal gland tumour (Mayr et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, p53 alterations have been detected in cases of mammary tumours (Van Leeuwen et al, 1996;Chu et al, 1998;Mayr et al, 1998;Mayr et al, 1999;Veldhoen et al, 1999;Muto et al, 2000), lymphoma (Veldhoen et al, 1998;Nasir and Argyle, 1999;Setoguchi et al, 2001), osteosarcoma (Van Leeuwen et al, 1997;Johnson et al, 1998;Setoguchi et al, 2001), thyroid tumour (Devilee et al, 1994;Setoguchi et al, 2001), papilloma (Mayr et al, 1994), skin tumours (Mayr et al, 1999), colon cancer (Setoguchi et al, 2001) and circumanal gland tumour (Mayr et al, 1997). However, apart from the above-mentioned colon cancer (Setoguchi et al, 2001) virtually no data are available regarding neoplasms of the small and large intestine.…”
mentioning
confidence: 99%
“…The p53 tumor suppressor gene encodes a protein which normally regulates cell cycle and programmed cell death, and its mutations are known to contribute to the carcinogenic process of various organs, including the mammary gland (Greenblatt et al, 1994). In CMT, p53 mutations have been detected in both benign and malignant types (Muto et al, 2000;Lee and Kweon, 2002;Kumaraguruparan et al, 2006).…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Mutation of the p53 gene plays an important role in the uncontrolled proliferation and resistance to apoptosis in cancer cells , leading to functional changes in proteins. In dogs, expression of the p53 gene was found in both benign (Muto et al, 2000) and malignant (Mayr et al, 1994;Veldhoen et al, 1999) tumors of mammary gland. Muto (2000) in his study showed no association between p53 expression and histological type of cancer, but claimed that this protein may play an important role in carcinogenesis and may be a negative prognostic factor (Muto et al, 2000).…”
Section: Discusionmentioning
confidence: 99%
“…In dogs, expression of the p53 gene was found in both benign (Muto et al, 2000) and malignant (Mayr et al, 1994;Veldhoen et al, 1999) tumors of mammary gland. Muto (2000) in his study showed no association between p53 expression and histological type of cancer, but claimed that this protein may play an important role in carcinogenesis and may be a negative prognostic factor (Muto et al, 2000). Chung-Ho (2004) came to a similar conclusion, arguing that the presence ofp53 in tumor cells is associated with their malignancy and bad prognosis in mammary gland tumors (Chun-Ho et al, 2004).…”
Section: Discusionmentioning
confidence: 99%